2015
DOI: 10.4314/ajtcam.v12i2.13
|View full text |Cite
|
Sign up to set email alerts
|

The investigations of total antioxidant status and biochemical serum profile in thymoquinone-treated rats.

Abstract: Background: This study was planned to determine the dosage and duration of thymoquinone (TQ) at which it demonstrates the optimum effect on the total antioxidant status (TAS) and the biochemical parameters in the blood serum. Materials and Methods: 48 male rats (Wistar-albino) weighing between 200-250 g were used as material. Group 1 (control) (TQ solution 5 mg/kg/day), Group 2 (15 mg/kg/day), Group 3 (30 mg/kg/day), Group 4 (45 mg/kg/day) and Group 5 (60 mg/kg/day) were designated, each containing 8 rats. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The oral dose of TQ (5 mg/kg/day) used in this study has been reported previously in several models of toxicity as an excellent protective daily dose in rats and mice (Al‐Zahrani, Mohany, Kandeal, & Badr, ; Kurt, Dede, & Ragbetli, ). TQ was dissolved in warm tap water (free from Pb) (65°C), and the resulting TQ solution was cooled at room temperature before oral administration.…”
Section: Methodsmentioning
confidence: 99%
“…The oral dose of TQ (5 mg/kg/day) used in this study has been reported previously in several models of toxicity as an excellent protective daily dose in rats and mice (Al‐Zahrani, Mohany, Kandeal, & Badr, ; Kurt, Dede, & Ragbetli, ). TQ was dissolved in warm tap water (free from Pb) (65°C), and the resulting TQ solution was cooled at room temperature before oral administration.…”
Section: Methodsmentioning
confidence: 99%
“…After the acclimation period, the rats were randomly divided into four groups of eight animals each and were treated for 5 weeks as follows: the control group received tap water; the Pb group received an aqueous solution containing 2,000 ppm of Pb acetate (0.2% w/v) ( 20 – 22 ); the Pb-TQ group was cotreated with Pb (as in the Pb group) plus TQ (5 mg/kg bw/day); and the TQ group received tap water and was given TQ (5 mg/kg bw/day) ( 23 – 25 ). TQ was administered by gastric tube daily between 8:00 and 9:00 am.…”
Section: Methodsmentioning
confidence: 99%
“…It was noted that serum globulin concentrations of chickens in N. sativa oil diet increased significantly (Bölükbaşı et al, 2009). In a study that determined the effects of TQ application on serum globulin levels, it was found that serum globulin levels increased significantly in the 60 mg/kg/day TQ applied group (p<0.05), however they stayed the same in 30 mg/kg/day TQ applied group (Kurt et al, 2015). It was observed in this study that TQ application did not change the total globulin level as well.…”
Section: Resultsmentioning
confidence: 42%
“…In a study that examined the effects of TQ application on serum total proteins, it was observed that the total protein levels increased in 60 mg/kg/day applied group (p < 0.05), and did not change in 30 mg/kg/day applied group (Kurt et al, 2015). It was further observed that, although the total protein concentrations relatively decreased in 30 mg/kg/day TQ applied group, but, this result was not important (p > 0.05) in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation